Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
Judge Leonard Meyers introducing the keynote speaker with Fresno County Young Lawyers Association President John McGregor looking on Star Palace lectern on table